Effect of NiCuZnFe2O4 on the microcrystalline properties of PVA/CMC polymer blends. (23rd February 2017) - Hemalatha, K.; Thejas Urs, G.; Mahadevaiah, D.; Somashekarappa, H.; Byrappa, K.; Somashekar, R.
Abstract : A series of PVA/CMC polymer composite films with different amounts of NiCuZnFe2 O4 (nickel–copper–zinc–ferrite) was prepared by means of solution-casting technique. These films were characterised using various techniques like X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), ultraviolet–visible spectroscopy (UV–visible) and AC electrical conductivity measurements. Recorded XRD pattern at room temperature shows an increase in amorphousity of the matrix with concentration of NiCuZnFe2 O4 nanoferrite. Microstructural parameters were computed using an in-house program employing XRD data. UV–visible spectra show that the optical absorption of the PVA/CMC nanocomposite films in the UV region is quite high. FTIR spectra show the stretching of the major vibration bands associated with organic–inorganic chemical groups present in the nanoferrite-doped polymer blends. Measured AC electrical conductivity of prepared samples shows that the added nanoferrite does increase the ionic conductivity at lower concentrations.